Differences in Cyberbullying Behavior of Instagram Social Media User Among Teenagers in Terms of Education Level - Meldawati; Rusli, Devi (CAUSALITA : Journal of Psychology, 2025)
This study aims to determine the differences in cyberbullying behavior of Instagram social media users in adolescents in terms of education level. This research design is comparative quantitative research. The sampling technique used is purposive sampling technique, with a sample of 108 teenagers who use Instagram in Padang city. The data in this study were analyzed by finding the mean and standard deviation, categorization and also the One-Way Anava parametric analysis test. The results showed that the anova test conducted obtained a value of p = 0.392 which means that p>0.05, meaning that the results in this study as a whole there is no difference in adolescents (junior high school, high school and college students in carrying out cyberbullying behavior. This means that the perpetrators of cyberbullying in adolescents at the junior high, high school and college education levels are not different. Teenagers do cyberbullying in each aspect, namely repetition, power imbalance and intention tend to be in the moderate category.